Al-âAsher School: the Philosophical Reflection of KH. Ahmad Dahlanâs Character Education - Khoirudin, Azaki; Anshori, Ari (Muhammadiyah University Press, 2018)
This article is a philosophical reflection of KH. Ahmad Dahlan educational practice. Based on the historical fact that KH. Ahmad Dahlan undertook the character education contained in Surah Al-Ashr to his students for 7-9 months. This educational practice is manifested in the form of âPengajian Wal-Ashriâ for young women and âWal-Ashri Cadre Schoolâ for male youth. This makes the spirit and ethos of al-Ashr embedded in young men and women, thus creating a